Knowledge, attitudes and practices of rural and suburban areas about brucellosis in Central Bosnia - Sabina Šečić-Selimović; Emsel Papić; Aida Katica; Mohammad Abou El Ardat; Zarema Obradović (Journal of Health Sciences)
Introduction: Brucellosis is a zoonosis classified as one of the most important neglected zoonoses in the world, especially in low and middle-income countries with livestock farming represented. In recent years, an increased incidence of brucellosis has been reported in Bosnia and Herzegovina, particularly in the Central Bosnia Canton (CBC) region. In the CBC region, the first case of the disease was registered at the end of 2002 in the municipality of Novi Travnik. In the period 2003-2012, 539 cases in humans and 7508 infected animals were registered. The aim of this study is to assess the knowledge, attitudes, and practices regarding the risk of brucellosis in the population living in rural and suburban areas because human behavior plays a significant role in the spread of brucellosis.